Dietary habits are a factor of healthy life of a society in the global world - M.S, Kulbaeva; S, Koshkimbayev K.; A.B. , Elantsev; L.B. , Umbetiyarova; I.M., Zharkova; R.M. , Shaikhynbekova; A., Zhuniszhan (International Journal of Psychosocial Rehabilitation, 2020)
A low level of functional education is a risk factor for lower levels of health literacy which in turn is considered to be a mediator in health results, currently representing an issue of interest in research on the management of the individual’s state of health. Objectives: To determine the effects of literacy on health through the mediation of dietary habits on nutritional status. Today, the biggest problem is overeating. People consume too many calories and poor quality foods, leading to chronic illnesses such as cancer, obesity, diabetes, or diseases of the cardiovascular system. Unlike scurvy, these diseases can not be easily dealt with. They do not appear acutely in one night, but develop over the years. And buying a box of oranges does not get rid of them. It is necessary to study the entire diet and lifestyle of the patient in order to weed out all the risk factors that lead to the disease. So the science of nutrition became inaccurate and confusing. A sea of conflicting studies has appeared, in which a lot of inaccuracies and limitations are easily discovered. Clutter in this area leads to nutritional confusion. Scientists cannot agree in any way, protect tomatoes from cancer or provoke it, red wine is useful or harmful, and so on. Therefore, journalists who write about nutrition often sit in a puddle, describing the next report.